2010
DOI: 10.1111/j.1556-4029.2010.01357.x
|View full text |Cite
|
Sign up to set email alerts
|

Child Sexual Abuse: Seven Years in Practice

Abstract: The purpose of this study was to determine the socio-demographic characteristics of sexually abused children. The records of 101 cases of child sexual abuse (CSA) were retrospectively evaluated. Socio-demographic characteristics of the victims, type of sexual abuse, and psychiatric diagnosis were studied. Of the victims, 56.4% (n = 57) were female and 43.6% (n = 44) were male. The mean age was 9.57 +/- 3.5, with a range of 4-17 years. Ninety-three (92.1%) of the victims had been admitted as part of the legal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 14 publications
3
29
0
7
Order By: Relevance
“…In our subjects, 56.8% of the children who were exposed to sexual abuse were found to be girls. Also in studies performed in Turkey, sexual abuse was reported to be more frequent in girls (7,10,12). In our study, 95% of physical abuse cases were reported to be punishment by slapping.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In our subjects, 56.8% of the children who were exposed to sexual abuse were found to be girls. Also in studies performed in Turkey, sexual abuse was reported to be more frequent in girls (7,10,12). In our study, 95% of physical abuse cases were reported to be punishment by slapping.…”
Section: Discussionmentioning
confidence: 57%
“…In a study performed in Turkey, sexual abuse was reported to be practiced frequently by a foreigner outside of the family which was similar to our study (10). In another study, sexual abuse was reported to be practiced most frequently by a familiar person outside of the family and by a foreigner in the second order of frequency (12).…”
Section: Discussionmentioning
confidence: 99%
“…A Turkish study retrospectively analysed 101 cases of CSA (of children aged 4-17) from records kept by a University Department of Child and Adolescent Psychiatry (Bahali et al, 2010); two-thirds of victims had been abused by someone they knew. Another Turkish study, also using records from a child psychiatric unit (n=83), similarly reported that the majority (73.5 per cent) of suspected perpetrators were known to the children, with 31.1 per cent being intrafamilial (Perdahli Fis et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Bahali et al (42) reported that the majority (66.3%) of the victims had been abused by an acquaintance, and 33.7% had been abused by a stranger. Another study by several institutions in Turkey reported that adolescents are more likely to be abused than children by someone known to them (54).…”
Section: Discussionmentioning
confidence: 99%
“…The severity and type of sexual abuse, the gender and age of the child and the offender, the relationship between the child and the offender, any accompanying physical abuse, and the frequency, number, and length of the abusive acts all seem to affect the child's outcomes (37,38,39,40,41,42). A previous study found that the victim's relationship with the abuser, the persistence and recurrence of the abuse, genital penetration, and the use of force or intimidation are associated with more adverse outcomes (43).…”
Section: Introductionmentioning
confidence: 99%